2008
DOI: 10.1097/mcg.0b013e318169c463
|View full text |Cite
|
Sign up to set email alerts
|

Use of Probiotic Bacteria for Prevention and Therapy of Allergic Diseases

Abstract: Probiotic bacteria as modulators of the immune response have been intensively studied in reducing the risk of immune-mediated diseases, including atopic diseases. Results from in vitro studies demonstrated that probiotics may modify the polarization of immune cells, supporting potential therapeutic effects in atopic diseases. Several clinical studies have been designed to explore the effective role of probiotics in the modulation of allergic diseases. The results of these studies, although promising, are not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 10 publications
2
22
0
1
Order By: Relevance
“…The majority of the RCTs showed a reduction in symptom severity and decreased use of relief medications [65,66]. Moreover, the immunomodulatory activity of the probiotic mixture VSL#3, studied in mouse models of allergic sensitization with inhalants, prevented the development of Parietaria major allergen-specific local and systemic response when delivered intranasally [59]. Twelve-month consumption of fermented milk containing Lctbs casei improved the health status of children with AR [67].…”
Section: Ige-sensitized (Atopic) Versus Non-ige-sensitized (Non-atopimentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the RCTs showed a reduction in symptom severity and decreased use of relief medications [65,66]. Moreover, the immunomodulatory activity of the probiotic mixture VSL#3, studied in mouse models of allergic sensitization with inhalants, prevented the development of Parietaria major allergen-specific local and systemic response when delivered intranasally [59]. Twelve-month consumption of fermented milk containing Lctbs casei improved the health status of children with AR [67].…”
Section: Ige-sensitized (Atopic) Versus Non-ige-sensitized (Non-atopimentioning
confidence: 99%
“…Studies in infants with eczema who received formulas supplemented with LGG have shown benefit in decreasing gastrointestinal symptoms [58]. In addition, oral therapy with the probiotic mixture VSL#3 and Lctbs casei strain Shirota were able to reduce anaphylactic symptoms in a food allergy model [59,60].…”
Section: Ige-sensitized (Atopic) Versus Non-ige-sensitized (Non-atopimentioning
confidence: 99%
“…124,125 Oral therapy with the probiotic mixture VSL#3 and Lactobacillus casei strain Shirota (LcS) were able to reduce anaphylactic symptoms in a food allergy model. 126,127 The therapeutic potential of VSL#3 probiotic mixture on specific immune responses and anaphylactic reaction induced in mice by the major food allergen shrimp tropomyosin was investigated. Oral therapeutic administration of VSL#3 to shrimp tropomyosin-sensitized mice significantly reduces symptom R e t r a c t e d score and histamine release in the feces following allergen challenge, as well as specific IgE response.…”
Section: Food Allergy and Anaphylaxismentioning
confidence: 99%
“…135,136 Moreover, the immunomodulatory activity of the probiotic mixture VSL#3, studied in the mouse models of allergic sensitization with inhalants, prevented the development of Parietaria major allergen-specific local and systemic response when delivered intranasally. 126 The aim of a study by Peng and Hsu 137 was to evaluate the efficacy of heat-killed Lactobacillus paracasei (LP33) in the treatment of perennial allergic rhinitis induced by house dust mite in 90 human subjects. The results suggest that heatkilled LP33 can effectively improve the overall quality of life for patients with allergic rhinitis and that it may be efficacious as an alternative treatment.…”
Section: Allergic Rhinitismentioning
confidence: 99%
“…A number of health claims have been associated with probiotics, such as reduced lactose intolerance, reduction in duration of infectious diarrhea, improved immune function, management of inflammatory bowel diseases, reduction in allergic responses, and lowering serum cholesterol (5,6,16,35,38,43,53,72). Given the increased clinical evidence supporting their role in health promotion, it is not surprising that there is an increasing demand for such functional foods within Europe (59).…”
mentioning
confidence: 99%